2020
DOI: 10.3390/polym12040901
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chromophoric Electron-Donating Groups on Photoinduced Solid-to-Liquid Transitions of Azopolymers

Abstract: The photoinduced solid-to-liquid transitions property of azobenzene-containing polymers (azopolymers) enables azopolymers with various promising applications. However, a general lack of knowledge regarding the influence of structure of the azobenzene derivatives on the photoinduced liquefaction hinders the design of novel azopolymers. In the present study, a series of azopolymers with side chains containing azobenzene unit bearing alkyl electron-donating groups were synthesized. The photoisomerization and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It was reported that the energy of the highest occupied molecular orbital ( E HOMO ) reflects the electron-donating ability of a molecule, and thus phenols with a higher E HOMO value were more susceptible to oxidation . As for the five phenols studied in this work, −Cl (−X) and −(CO)– are electron-withdrawing groups with the electron-withdrawing capacity of −(CO)– greater than that of −Cl, while −R is an electron-donating group. , The presence of electron-withdrawing groups decreased the E HOMO value, which will enhance the stability of compounds toward oxidation . By contrast, the electron-donating groups can increase a compound’s reactivity with ferrate­(VI).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…It was reported that the energy of the highest occupied molecular orbital ( E HOMO ) reflects the electron-donating ability of a molecule, and thus phenols with a higher E HOMO value were more susceptible to oxidation . As for the five phenols studied in this work, −Cl (−X) and −(CO)– are electron-withdrawing groups with the electron-withdrawing capacity of −(CO)– greater than that of −Cl, while −R is an electron-donating group. , The presence of electron-withdrawing groups decreased the E HOMO value, which will enhance the stability of compounds toward oxidation . By contrast, the electron-donating groups can increase a compound’s reactivity with ferrate­(VI).…”
Section: Resultsmentioning
confidence: 64%
“…28 As for the five phenols studied in this work, −Cl (−X) and −(C�O)− are electron-withdrawing groups with the electron-withdrawing capacity of −(C�O)− greater than that of −Cl, while −R is an electron-donating group. 29,30 The presence of electron-withdrawing groups decreased the E HOMO value, which will enhance the stability of compounds toward oxidation. 31 By contrast, the electron-donating groups can increase a compound's reactivity with ferrate(VI).…”
Section: Removal Of the Five Phenolic Compounds Bymentioning
confidence: 99%
“…These asymmetric molecules have been carefully discussed in a study by Akiyama et al 17 The introduction of this asymmetric methyl can weaken the π-π interaction in the molecule, which weakens the compactness of the molecular packing. 18 The introduction of this asymmetric methyl also weakens the H-aggregation in the molecules. 19 The introduction of long alkyl chains at both ends increases the flexibility of azobenzene molecules, and makes azobenzene molecules more prone to photoisomerization.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22][23][24] They absorb ultraviolet (UV) and/or visible light, and molecular photoisomerization occurs. The isomerization is sometimes accompanied by a solid-liquid transition, 25,26 and the transition energy can be stored by light irradiation. [27][28][29][30] The combination of cold crystallization and photoisomerization is a promising method for nding new functional energy storage systems.…”
Section: Introductionmentioning
confidence: 99%